Numerical investigation of thermo-hydraulic performance of an opposed piston opposed cylinder engine water jacket with helical fins. (August 2019) - Hu, Xiaoyu; Sun, Qiang; Li, Guoxiang; Bai, Shuzhan
Highlights: A comprehensive CFD model was proposed to study OPOC engine thermal status. Effect of pitch height on thermal-hydraulic performance was studied. A thermal performance factor was adopted to identify optimal pitch height. Abstract: In this paper, the thermo-hydraulic performance of an opposed piston opposed cylinder (OPOC) cylinder water jacket with helical fins on the annulus side was studied experimentally and numerically. Three dimensional computational fluid dynamics (CFD) software FLUENT has been adopted to explore fluid flow characteristics, pressure drop and cylinder wall temperature under different configurations. Four different cases of helical fin pitch (154 mm, 170 mm, 184 mm and 205 mm) were analyzed under same flow rate, of which the values of Reynolds number are all in turbulent region. The numerical model was first validated by comparison with Particle Image Velocity (PIV) experiment result. Then heat transfer validation was conducted using a double-pipe heat exchanger with longitudinal fins and the results were compared with empirical correlation. The validated model was used to calculate the thermo-hydraulic performance of OPOC cylinder water jacket of four different cases. The results showed that compared with cylinder water jacket without helical fins, configurations with helical fins increased heat transfer performance obviously and the pressure drop went up in the same time. A comprehensive thermal performance factor which takes into account both heat transfer and pressure drop was defined to analyze different cases, and the case with fin pitch of 187 mm performed optimal thermal performance.